A novel green reinforcement corrosion inhibitor extracted from waste Platanus acerifolia leaves. (10th November 2020) - Liu, Qingyang; Song, Zijian; Han, Han; Donkor, Saddick; Jiang, Linhua; Wang, Wanyi; Chu, Hongqiang
Graphical abstract: Highlights: A novel green corrosion inhibitor was prepared from the waste PAL. The PAL extract was conformed as an efficient mixed type corrosion inhibitor. QM/MD simulations based on UPLC-MS supported the donor–acceptor adsorption and inhibition mechanism for PAL extract. XPS provided the formation evidence of the carbonaceous/nitrogenous film on steel surface. Abstract: In this study, an environmentally friendly corrosion inhibitor was prepared from waste Platanus acerifolia leaves (PAL) for reducing the chloride-induced reinforcement corrosion. Four extraction methods were employed in the preparation work. The inhibiting performances of the four types of PAL extracts and two benchmark inhibitors were studied by various electrochemical measures. After that, the optimal group was obtained (extract #4, prepared by an ultrasonic-assisted alkali-pretreated ethyl extraction method) and analyzed with ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) to determine its main chemical constituents. The inhibition/adsorption mechanism was analyzed via X-ray photoelectron spectroscopy (XPS) as well as the quantum mechanics and molecular dynamics simulations. According to the results of electrochemical experiments, the PAL extract is an excellent mixed type inhibitor that restrains both the cathodic and anodic reactions. UPLC-MS results provided the existence evidence of more than ten kinds of flavonoids or oligopeptides in the PAL extract. XPS and simulation results indicated that these flavonoids/oligopeptides exerted their inhibition effect by generating a nitrogen-carbon film on the steel substrate via the donor–acceptor interactions of reactive sites.